Surgical Management of Glaucoma in Eyes with Ocular Cicatricial Pemphigoid - Kolipaka, Gowri Pratinya; Gebremichael, Bayu Guteta; Dixit, Siddharth; Basu, Sayan; Senthil, Sirisha (Nepalese Journal of Ophthalmology, 2024)
Introduction: Glaucoma in ocular cicatricial pemphigoid (OCP) is an important blinding complication. Glaucoma in eyes with OCP is most often managed medically as surgical management is difficult in eyes with cicatrised conjunctiva and often end up with complications or scarring and failure. In some cases where the topical antiglaucoma medications are not tolerated or worsen the OCP and in eyes with medically uncontrolled glaucoma, surgical management would be needed. The glaucoma drainage devices (GDD) are more suitable in these eyes compared to trabeculectomy in these eyes. Case: Here two cases of a 35-year old and 62-year old males with biopsy proven OCP and steroid-induced medically uncontrolled glaucoma that were successfully managed with Ahmed glaucoma valve are reported. Observation: Performing an implant in an eye with poor ocular surface is a challenge. Appropriate modifications need to be performed to overcome these challenges. In this report, the surgical challenges and post-operative management have been highlighted. Conclusion: Despite intraoperative and post-operative challenges of performing glaucoma surgery in eyes with OCP, preoperative planning, meticulous surgery, and post-operative follow-up would go a long way in successfully managing refractory glaucoma in these patients.